Hybrid optimal path traceback system development for optimizing DNA sequences alignment: article - Ahmad Sabri, Nur Dalilah (2012)
This paper present the new hybrid optimal path trace back system development for solving optimal path trace back complexity issue. The objective of this paper is to study several optimization techniques and determine the best optimization technique for optimizing the optimal path trace back system. Therefore, two designs are proposed and analyzed for in this study. The project is divided in two stages which are theoretical and experimental design. In theoretical design, the proved of concept for the proposed design is calculated based on mathematical equation which defined by Smith-Waterman algorithm. Design construction which covers code development, compilation and simulation is carried out under experimental design for both of the proposed designs using Altera Quartus II version 9.0 EDA tools and targeted to Cyclone II EP2C35 FPGA at 100MHz clock cycle. As a result, the second design required three times design area as compare to the first design for determine the optimal path for the same matrix size. Therefore, the first design is the best hybrid approach for the optimal path trace back size since theoretical result has shown both of the design has the same output but the second design suffers in terms of large design area.